2012
DOI: 10.1111/j.1399-3054.2012.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and speciation of Mn in hydrated roots of cowpea at levels inhibiting root growth

Abstract: The phytotoxicity of Mn is important globally due to its increased solubility in acid or waterlogged soils. Short-term (≤24 h) solution culture studies with 150 µM Mn were conducted to investigate the in situ distribution and speciation of Mn in apical tissues of hydrated roots of cowpea [Vigna unguiculata (L.) Walp. cv. Red Caloona] using synchrotron-based techniques. Accumulation of Mn was rapid; exposure to 150 µM Mn for only 5 min resulting in substantial Mn accumulation in the root cap and associated muci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Analysis using XAS identified most Mn in shoots as Mn(II) complexed with malate or citrate, indicating Mn(II) to be the major form translocated via the xylem. This is consistent with the rapid uptake of Mn by cowpea (Kopittke et al, 2013) and the transport of 54 Mn via the transpiration stream in white lupin (Page et al, 2006). In this study, therefore, responses of species to high Mn were not related to Mn concentration or speciation in roots and stems.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Analysis using XAS identified most Mn in shoots as Mn(II) complexed with malate or citrate, indicating Mn(II) to be the major form translocated via the xylem. This is consistent with the rapid uptake of Mn by cowpea (Kopittke et al, 2013) and the transport of 54 Mn via the transpiration stream in white lupin (Page et al, 2006). In this study, therefore, responses of species to high Mn were not related to Mn concentration or speciation in roots and stems.…”
Section: Discussionsupporting
confidence: 86%
“…Few studies, however, have used synchrotronbased techniques to investigate the mechanisms of Mn toxicity and tolerance in agronomic species despite their importance for food production in regions where soils are acidic or intermittently waterlogged. One study on cowpea, with a critical toxicity concentration of only 2 mM Mn (Edwards and Asher, 1982), has shown an accumulation of Mn-citrate in the root cap and associated mucigel within 5 min of exposure to 150 mM Mn (Kopittke et al, 2013).…”
mentioning
confidence: 99%
“…Using S-XRF with a fast detector, the As distribution has been imaged in fresh hydrated roots of cowpea (Vigna unguiculata) following short-term exposure to either As(III) or As(V), showing a strong accumulation of As in the region that is likely to be endodermis and/or pericycle cells [36] (Figure 2C). The same approach has been applied to mapping the in situ distribution of Zn, Cu, Ni, Mn, and Se in hydrated tissues [17,[37][38][39]. A recent study combining S-XRF and NanoSIMS has revealed that As is localized in the vacuoles of the companion cells within the phloem of various types of vascular bundles of the rice node, internode, and leaf sheath [14] ( Figure 2D,E).…”
Section: Trends In Plant Sciencementioning
confidence: 99%
“…1, D and E), suggesting that detoxification of internal Mn might be required for S. guianensis to tolerate Mn (Dou et al, 2009;Fernando et al, 2010;Kopittke et al, 2013). For example, with the help of x-ray absorption near-edge spectroscopy and extended x-ray absorption fine-structure spectroscopy techniques, malate has been demonstrated to chelate internal Mn within the leaf tissues in Gossia bidwillii (Fernando et al, 2010).…”
Section: Fine-stem Has Superior Mn Tolerancementioning
confidence: 99%
“…For example, with the help of x-ray absorption near-edge spectroscopy and extended x-ray absorption fine-structure spectroscopy techniques, malate has been demonstrated to chelate internal Mn within the leaf tissues in Gossia bidwillii (Fernando et al, 2010). Furthermore, in the roots of cowpea and leaves of Phytolacca acinosa, it has been estimated that 80% and 90% of internal Mn can be bound in complexes with citrate and oxalate, respectively (Xu et al, 2009;Kopittke et al, 2013). Therefore, in this study, changes in the internal concentrations of malate, oxalate, and citrate in response to Mn toxicity were examined in both S. guianensis genotypes.…”
Section: Fine-stem Has Superior Mn Tolerancementioning
confidence: 99%